Estudo do processo de rosqueamento com macho de corte de metal duro em ferro fundido vermicular - Mota, Paulo Rosa da (2009)
The use of compacted graphite iron - CGI is growing in the automobile industry, replacing several components that usually are manufactured in grey cast iron. However, due to its poor machinability when compared to grey cast iron, the production cost sometimes is not competitive. Several research about machinability of CGI has already been developed, mainly in turning, milling and drilling operations. Little has been done with regards to tapping process, which is a more complex operation. The main objective of this work is the investigation of the performance of cemented carbide taps when cutting CGI 450 ASTM. It was is used M13x1,5 taps with four straight flutes, TiAlN coated. The tests were carried out in dry conditions and using cutting fluid applied by MQF (minimal quantity of fluid) and overhead flow. The work was split into two parts. In the first, the cutting tools were used in the production line of Tupy S.A., to produce different wear levels. The second part was developed at the laboratory, when tool wear was measured and experiments were carried out to obtain cutting forces and torque. The results showed that the cutting forces and torque depend on the cutting parameters. Analysis in the scanning electron microscope and optical microscope to determine the wear mechanisms suggested that the main wear mechanisms are adhesion and abrasion. Experiments were also carried out to study the effect of some important aspects of the process like concentricity, feed rate, thread length and tool defects.